2014
DOI: 10.3390/toxins6072097
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Cyclodextrin Pore Blocker Protects Mammalian Cells from Clostridium difficile Binary Toxin CDT

Abstract: Some Clostridium difficile strains produce, in addition to toxins A and B, the binary toxin Clostridium difficile transferase (CDT), which ADP-ribosylates actin and may contribute to the hypervirulence of these strains. The separate binding and translocation component CDTb mediates transport of the enzyme component CDTa into mammalian target cells. CDTb binds to its receptor on the cell surface, CDTa assembles and CDTb/CDTa complexes are internalised. In acidic endosomes, CDTb mediates the delivery of CDTa int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 82 publications
0
16
0
Order By: Relevance
“…Possible candidates are tailored azolopyridinium salts and tailored cyclic dextrines [33,34,35,36]. In previous studies, we have demonstrated that low concentrations of chloroquine were able to inhibit intoxication of target cells by C2-toxin in cell-based assays and pore-formation by C2IIa in lipid bilayer membranes [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Possible candidates are tailored azolopyridinium salts and tailored cyclic dextrines [33,34,35,36]. In previous studies, we have demonstrated that low concentrations of chloroquine were able to inhibit intoxication of target cells by C2-toxin in cell-based assays and pore-formation by C2IIa in lipid bilayer membranes [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…This chapter has provided a vivid example of one of the first successful designs of such wide-spectrum antitoxins. Indeed, the custom-synthesized, positively charged polyvalent cyclodextrin-based AMBnTβCD compound was shown to be protective against the cytotoxicity induced by four different toxins: anthrax toxins of B. anthracis [104], clostridial C2, iota [106], and CDT toxins [84]. The universality idea is easy to perceive and appreciate because a potent, wide-spectrum antidote would be expected to be active against more than one virulent agent.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple compounds, which are charged positively at mildly acidic pH values, were shown to interact with PA 63 , C2IIa, and Ib channels incorporated into planar bilayers [38,67,72,74,75,83,84] (Figure 38.2). The ability of tetraalkylammonium ions to translocate through PA 63 , reversibly blocking the K + current [76,85,86], was used to estimate the minimum physical size of the PA 63 pore lumen to be about 12 Å.…”
Section: Small-molecule Cationic Pore Blockersmentioning
confidence: 99%
See 2 more Smart Citations